Semantics of the Word Imlâq (Tafsir Muqâran between QS. al-An'am:151 and QS. al-Isra': 31) - Amnesti, Muhammad Esa Prasastia; Thobroni, Ahmad Yusam; Ihkamuddin, Hazmi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study discusses the phenomenon of child murder, both born and abortion due to poverty reasons and will be more burdensome family life. The problem in this study is the semantics (meaning) of the word imlâq in the interpretation of QS. al-An'am:151 and QS. al-Isra': 31? This type of research is literature. Sources of data come from the Qur'an and books of interpretation. The results of the study show that the semantics of the word imlâq in the two letters above both mean the prohibition of killing children because of (worried) poverty. The difference, QS. al-An'am emphasized the concern of poverty on the part of his parents, which makes life increasingly difficult if the child is born, refuted by Allah by providing sustenance guarantees to his parents by using the sentence structure "nahnu narzuqukum wa innahum" by prioritizing the pronoun "kum" as the initial " parent". While QS. al-Isra': 31 emphasizes the concern of poverty on the part of the child when he is born, refuted by Allah by providing a guarantee for the child's sustenance by using the sentence structure "nahnu narzuquhum wa iyyakum" by prioritizing the pronoun "hum" as the initial "children." Thus there is no justification for the act of killing a child.